A transcriptional response of Clostridium beijerinckii NRRL B-598 to a butanol shock - Sedlar, Karel; Kolek, Jan; Gruber, Markus; Jureckova, Katerina; Branska, Barbora; Csaba, Gergely; Vasylkivska, Maryna; Zimmer, Ralf; Patakova, Petra; Provaznik, Ivo (Biotechnology for biofuels, 2019)
BACKGROUND: One of the main obstacles preventing solventogenic clostridia from achieving higher yields in biofuel production is the toxicity of produced solvents. Unfortunately, regulatory mechanisms responsible for the shock response are poorly described on the transcriptomic level. Although the strain Clostridium beijerinckii NRRL B-598, a promising butanol producer, has been studied under different conditions in the past, its transcriptional response to a shock caused by butanol in the cultivation medium remains unknown. RESULTS: In this paper, we present a transcriptional response of the strain during a butanol challenge, caused by the addition of butanol to the cultivation medium at the very end of the acidogenic phase, using RNA-Seq. We resequenced and reassembled the genome sequence of the strain and prepared novel genome and gene ontology annotation to provide the most accurate results. When compared to samples under standard cultivation conditions, samples gathered during butanol shock represented a well-distinguished group. Using reference samples gathered directly before the addition of butanol, we identified genes that were differentially expressed in butanol challenge samples. We determined clusters of 293 down-regulated and 301 up-regulated genes whose expression was affected by the cultivation conditions. Enriched term "RNA binding" among down-regulated genes corresponded to the downturn of translation and the cluster contained a group of small acid-soluble spore proteins. This explained phenotype of the culture that had not sporulated. On the other hand, up-regulated genes were characterized by the term "protein binding" which corresponded to activation of heat-shock proteins that were identified within this cluster. CONCLUSIONS: We provided an overall transcriptional response of the strain C. beijerinckii NRRL B-598 to butanol shock, supplemented by auxiliary technologies, including high-pressure liquid chromatography and flow cytometry, to capture the corresponding phenotypic response. We identified genes whose regulation was affected by the addition of butanol to the cultivation medium and inferred related molecular functions that were significantly influenced. Additionally, using high-quality genome assembly and custom-made gene ontology annotation, we demonstrated that this settled terminology, widely used for the analysis of model organisms, could also be applied to non-model organisms and for research in the field of biofuels.
Keywords: RNA-Seq transcriptome; Butanol shock; Clostridium beijerinckii NRRL B-598; ABE fermentation